ANALISIS PRODUKSI PADI ORGANIK LAHAN RAWA DI KABUPATEN HULU SUNGAI UTARA PROPINSI KALIMANTAN SELATAN - Purna Kusumayana; Andi Suci Anita (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2017)
Healthy lifestyle has become a new trend to leave the old life patterns that use non-natural chemicals. Such as fertilizers, synthetic chemical pesticides and growth hormones in agricultural production. The point people began to realize, healthy and nutritious food that is high can only be produced with the new method, known as organic farming.  The purpose of the study these are (1) identify the factors that influence the production of organic rice swamps, (2) analyze the efficiency of the use of factors of production in order to create an organic rice production swamp land in Hulu Sungai Utara. The results showed that the value of F count larger than F table with F significant 0,000 <0,05 so that H0 rejected and H1 accepted. This means that the variable land, labor and seeds together real impact on rice production. While the t test, factors that significantly affect the organic rice production is labor and land. The efficiency value of 0.47 and a price of economic efficiency value of 0.35 it does show that rice farming is not efficient because it is worth < 1, and is therefore necessary to add the use of production factors